Shaping a positive occupational safety climate in general practice teams—findings of the baseline survey of the cluster randomized IMPROVEjob trial - Wagner, Anke; Rind, Esther; Burgess, Stephanie; Böckelmann, Irina; Thielmann, Beatrice; Heinz, Helen; Siegel, Achim; Schröder, Verena; Jöckel, Karl-Heinz; Hüsing, Anika; Pieper, Claudia; Eilerts, Anna-Lisa; et al. (Frontiers in Public Health, 2025)
IntroductionThe consideration of occupational health and safety can support the creation of good sustainable working conditions in general practices and help in retaining staff and support their workability. This study aimed to assess attitudes of primary care physicians and practice assistants toward occupational safety climate, and to identify what factors are associated with a perceived positive occupational safety climate in this setting. The identification of such factors in general practice settings can serve as a basis for further developments of specific tailored interventions and offers to promote workplace safety for GPs and practice assistants.MethodsThis study is based on baseline data of a cluster randomized controlled trial (IMPROVEjob study): 84 practice owners, 28 employed physicians, and 254 practice assistants from 60 German general practices took part in a standardized survey. Occupational safety climate was measured with items from previous studies. Standardized and validated items regarding working conditions, work behavior, general health, burnout and chronic stress were also included. All statistical analyses were performed with IBM SPSS version 28, and comprised descriptive analyses, Mann–Whitney-U-test and Kruskal-Wallis test, as well as a stepwise multiple regression analysis considering cluster effects.ResultsWe found a positive perception of occupational safety climate across all occupational groups, for example regarding the role of the direct supervisor in occupational safety at work or the occupational safety commitment of the practice. Bivariate analysis mainly revealed associations between occupational safety climate and several aspects of working conditions. The regression model revealed the following important factors for perceived positive occupational safety climate (assessed by the scale company standards): supervisor support for occupational safety (β = 0.43) and job satisfaction (β = 0.22).DiscussionLeadership and job satisfaction were identified as main factors shaping a positive occupational safety climate (scale company standards) in our regression model built on data from German general practices and their practice teams. The findings are consistent with a previous study conducted in the German healthcare setting. The promotion of these factors should be supported further and can probably contribute to improving the occupational safety climate in general practices in Germany.